FORMULASI PENAMBAHAN AMPAS TAHU TERHADAP KANDUNGAN KIMIA DAN AKSEPTABILITAS PRODUK OTAK-OTAK IKAN TENGGIRI - Dewi Sartika; Asriyanti Syarif (AGROINTEK, 2016)
Tofu waste is a side product that obtained from the manufacturing of tofu. Substitute soy pulp out on making local dish called "otak-otak" of mackerel is an idea to utilize the waste processed out and also improve the nutritional and economic value.The aim of this study is to determine the formulation of the addition of tofu waste right to produce otak-otak by the chemical content, acceptability of the best and economic value. The research method is by adding tofu waste with treatment A1: 100gr Tofu Dregs; A2: 200gr Tofu Dregs; A3: 300gr Tofu Dregs, in the manufacture of otak-otak mackerel.The results showed that the addition of tofu waste for the formulation in the manufacture of otak-otak mackerel are best in terms of chemistry and economics is the treatment and A3 by adding 300gr of pulp, the best in terms of acceptability is A2 treatment with the addition of 200gr tofu waste.